QUANTIFICATION OF HYDRAULIC CHARACTERISTICS OF SWELLING MATERIAL - Boris Kavur; Jasmin Jug; Biljana Kovačević Zelić; Ivan Vrkljan (Rudarsko-geološko-naftni Zbornik)
This paper presents a laboratory and numerical study to determine three hydraulic characteristic curves of a swelling material (soil or rock) in which montmorillonite is the predominant type of mineral. The first, the soil-water characteristic curve, represents the relationship between suction and moisture content that needs to be defined to solve the water flow problem and the accompanying change in the volume of the swelling unsaturated porous medium. The second curve presents hydraulic conductivity as a function of saturation or suction. The third curve represents the relationship between the volume change and the moisture content of the swelling material. These curves are crucial for understanding water flow and volume changes in swelling materials, with this study focusing on wetting regime behaviour. The aim of this research was to establish reliable methods for the definition of the hydraulic properties of the swelling material and to verify a proposed swelling model. While the swelling material shows significant hysteresis between the drying and wetting regimes, the hydraulic conductivity function shows little or no hysteresis between drying and wetting paths at equal moisture contents (coefficients).